2021
DOI: 10.1109/access.2021.3082638
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Segmentation and Intuitive Visualisation of the Epiretinal Membrane in 3D OCT Images Using Deep Convolutional Approaches

Abstract: Epiretinal Membrane (ERM) is a disease caused by a thin layer of scar tissue that is formed on the surface of the retina. When this membrane appears over the macula, it can cause distorted or blurred vision. Although normally idiopathic, its presence can also be indicative of other pathologies such as diabetic macular edema or vitreous haemorrhage. ERM removal surgery can preserve more visual acuity the earlier it is performed. For this purpose, we present a fully automatic segmentation system that can help th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…We implemented not only standardized horizontal OCT scans but also vertical and oblique oriented ones. In addition to treating ERM detection as a classification task as in this study, segmentation algorithms have also been trained to detect ERMs [16,17,18]. Some of these works have primarily is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) focused on the detection of the internal limiting membrane (ILM), which might be erroneous in eyes with a visible vitreous or posterior vitreous limiting membrane -as regularly seen in patients with ERM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We implemented not only standardized horizontal OCT scans but also vertical and oblique oriented ones. In addition to treating ERM detection as a classification task as in this study, segmentation algorithms have also been trained to detect ERMs [16,17,18]. Some of these works have primarily is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) focused on the detection of the internal limiting membrane (ILM), which might be erroneous in eyes with a visible vitreous or posterior vitreous limiting membrane -as regularly seen in patients with ERM.…”
Section: Resultsmentioning
confidence: 99%
“…For medical reasons, it is similarly important to detect early and low-grade stages of ERMs. Finally, some studies have reported success in automatically segmenting ERMs via DNNs trained on small data sets [16, 17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…The final dataset for each experiment where we will study the sex and age factors was divided into mutually exclusive subsets, being (60%, 20%, and 20%) for training, validation, and testing, respectively. Regarding the training, we started from the DenseNet-161 model pre-trained with the ImageNet [27] dataset, making use of the transfer learning strategy, but modifying the output layer to adapt it to our specific classification problem. In this way, the training process will be more efficient due to the faster convergence of the training and validation curves.…”
Section: Training Detailsmentioning
confidence: 99%
“…In this work, we present an automatic methodology for the segmentation of the ERM in OCT volumes by using deep learning. This methodology consists of three phases, corresponding to the detection of the region of interest, the segmentation of the ERM via the classification of window samples of the ILM, and the visualisation and post-processing of the segmentation map [7]. This process produces a representation of the ERM presence and absence over the eye fundus in the form of a 2D colour map.…”
Section: Introductionmentioning
confidence: 99%